The stress–energy tensor for polyharmonic maps. (January 2020) - Branding, Volker
Abstract: We derive the stress–energy tensor for polyharmonic maps between Riemannian manifolds. Moreover, we employ the stress–energy tensor to characterize polyharmonic maps where we pay special attention to triharmonic maps.